(NrAZNYE DNI WOJNY(B. (NdNEWNIK PISATELQ(B: [(NbIOGRAFIQ(B]; s 1942-1945 (NGODY(B: (NtOM (B2 / s (N~ASTX (B9s - (NsIMONOW(B, (NkONSTANTINs ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1983)
(Nw DEWQTOM TOME POME]ENY WOENNYE DNEWNIKOWYE ZAPISI(B, (NOHWATYWA@]IE SOBYTIQ (B1942-1945 (NGODOW(B.s
rus
Keywords: (NdNEWNIKIs; (NbIOGRAFIQs